Cultural Dimensions of Learning in Online Teacher Education Courses - Anthony Neil Hunt; Sue Tickner (Flexible Learning Association of New Zealand, 2015)
Aotearoa New Zealand's demographics are changing rapidly and, as a consequence, there is now greater diversity in the tertiary student population. This diversity is evident in the continuing growth of Māori and Pasifika student participation. Teacher education is increasingly emphasising social competencies and intercultural awareness. Online pedagogies based on sociocultural methods require openness to difference, understanding, and sharing; but it is a challenge to support productive learning communities that span diverse cultural backgrounds. This study began with a literature review, and then the eight dimensions in the cultural dimensions of learning framework (CDLF; Parrish & Linder-VanBerschot, 2010) survey were modified for use with online courses. The modified survey was trialled with 112 students and four lecturers in 11 online teacher education courses offered by a New Zealand university. Although respondents exhibited a wide range of choice in the survey, the participants were not sufficiently diverse to reveal any differences that might be attributed to culture. It was concluded that the CDLF could provide a useful stimulus to promote discussion amongst learners and teachers and that this discussion could raise awareness of the diversity of approaches to learning that could have a cultural basis. However, the lack of attention to indigenous worldviews and the limited evidence of reliability in the CDLF scales suggest that further empirical research of this survey instrument is unlikely to be worthwhile.